Impaired Terminal Differentiation Of Pulmonary Macrophages in a Guinea Pig Model of Chronic Ethanol Ingestion - Brown, Sheena D. (2009)
Alcoholic patients have an increased risk of respiratory infections, which is partially due to an impaired immune response of alveolar macrophages. The mechanisms by which alcohol impairs alveolar macrophage function are poorly understood. In this study, we demonstrated in a guinea pig model that chronic ethanol ingestion significantly impaired alveolar macrophage differentiation and function. Isolated alveolar macrophages were separated into 4 different subpopulations with varying densities and levels of maturation. Compared to control values, chronic ethanol ingestion decreased the percentage of alveolar macrophages in the mature fractions by ~60%. Alveolar macrophage function in each subpopulation was determined by measuring phagocytosis of FITC-labeled S. aureus. Alveolar macrophages from ethanol-fed animals had ~80% decrease in the phagocytic index. Western blot and immunohistochemical analysis of the differential markers GM-CSF receptor α (GM-CSFR-α), PU.1, CD11c, and CD11b verified that alcoholic macrophages displayed impaired terminal differentiation. While oral supplementation with the glutathione precursor S-adenosyl-methionine (SAM) did not alter the maturational status of control animals, SAM s supplementation shifted the distribution of macrophages to more mature fractions, normalized the phagocytic index; as well as normalized expression of CD11c, CD11b, PU.1, and GM-CSFR-α. Chronic ethanol ingestion also impaired the differentiation status of interstitial macrophages which was normalized by SAM supplementation. This improvement in the maturational status suggested that ethanol-induced oxidant stress is a central feature in impaired terminal differentiation of macrophages in the interstitial and alveolar space. Therefore, strategies targeting pulmonary oxidant stress may restore macrophage differentiation and function even after chronic ethanol ingestion.